Light chain amyloidosis: Where are the light chains from and how they play their pathogenic role?. Issue 4 (July 2017) - Zhang, Chunlan; Huang, Xufei; Li, Jian
Abstract: Amyloid light-chain (AL) amyloidosis is a plasma-cell dyscrasia, as well as the most common type of systematic amyloidosis. Pathogenic plasma cells that have distinct cytogenetic and molecular properties secrete an excess amount of amyloidogenic light chains. Assisted by post-translational modifications, matrix components, and other environmental factors, these light chains undergo a conformational change that triggers the formation of amyloid fibrils that overrides the extracellular protein quality control system. Moreover, the amyloidogenic light-chain itself is cytotoxic. As a consequence, organ dysfunction is caused by both organ architecture disruption and the direct cytotoxic effect of amyloidogenic light chains. Here, we reviewed the molecular mechanisms underlying this sequence of events that ultimately leads to AL amyloidosis and also discuss current in vitro and in vivo models, as well as relevant novel therapeutic approaches.